Exploring the Dynamics of Local Cultural Change in Cintanagara: Between Tradition and Modernity - Irma Dwi Kartika; Egi Nurholis (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
The study aims to explore the dynamics of local cultural change in the Cintanagara community, focusing on the interaction between tradition and modernity. The community has experienced significant socio-cultural changes due to technological advances. These changes have affected various aspects of life, including social, economic, and cultural aspects. The research examines how modernization affects the existence of traditions and ancestral heritage in Cintanagara. In addition, the research also explores how the community adapts modernity to local culture, creating a unique identity. The research was conducted to understand how local communities preserve local wisdom amid changing times. Descriptive qualitative research methods were used through data reduction to explore the dynamics of local cultural change in the Cintanagara community between tradition and culture. The results of the study are expected to provide insights into cultural change in the Cintanagara community, as well as strategies to strengthen and preserve culture in accordance with the needs and demands of the times.